Analisis Pengaruh Independensi Dan Kompetensi Auditor Internal Terhadap Kualitas Audit : Literature Review - Mardiana Sartika Dewi; Daniswara Nursyahbani; Ana Naimatul Janah; Chalida Nur Rahmadiyani; Herlina Manarung (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
In an entity or company to support the creation of good financial reports must have a good internal auditor. Internal auditors within the company play a role as a party that evaluates and provides input so that the financial statements to be presented are of high quality. An independent attitude must be possessed by an auditor. Competent auditors are also needed to be able to produce quality audit reports. This research was made to provide knowledge about the effect of independence and competence on audit quality. The research method used is a literature review. The results of the research show that independence and competence have a significant impact on audit quality.